Pengupahan Jasa Host Live Streaming Tiktok Shop Perspektif Teori Relasi Kuasa dan Akad Ijarah - Aprilia, Via; Huda, Muhammad Chairul (TAWAZUN: Journal of Sharia Economic Law, 2023)
The purpose of this study is to find out how the Tiktok shop live streaming hosting service remuneration system is based on the perspective of Michel Foucault's power relations theory and the ijarah contract. The type of research used is field research with qualitative methods and uses a descriptive analysis approach. Data collection techniques by way of observation and interviews. Data findings in the form of research facts that are logically and systematically outlined and then analyzed are used as conclusions from the research. The results of this study are the power relations that occur between the employees of the live streaming Tiktok shop host and the owner of the Gemaz Salatiga Shop in line with the power relations theory coined by Michel Foucault regarding power and knowledge. This is evidenced by the behavior and decisions that are applied by the owner of the Gemaz Salatiga Store to employees such as determining the work system, working time and determining the wage system. Then the analysis uses the ijarah contract, the Tiktok shop live streaming host fee system is included in the ijarah al-amal contract. Judging from the terms and pillars of the ijarah contract, the Tiktok shop live streaming host fee system has been fulfilled. However, the principle of fairness should be a reference for the rulers of live host streaming services.